Ultrasound-enhanced enzymatic hydrolysis of poly(ethylene terephthalate). (October 2016) - Pellis, Alessandro; Gamerith, Caroline; Ghazaryan, Gagik; Ortner, Andreas; Herrero Acero, Enrique; Guebitz, Georg M.
Graphical abstract: Enzyme-catalyzed hydrolysis of poly(ethylene terephthalate) using conventional and ultrasound energy (USe). The use of USe as heat source lead to an 6.6-fold increase of the released degradation products. Highlights: Ultrasound-enhanced cutinase activity towards PET hydrolysis is reported. Ultrasonic activation is more effective when higher polymer surface is available. A negative effect of polymer crystallinity on enzymatic hydrolysis was observed. Abstract: The application of ultrasound was found to enhance enzymatic hydrolysis of poly(ethylene terephthalate) (PET). After a short activation phase up to 6.6 times increase in the amount of released products was found. PET powder with lower crystallinity of 8% was hydrolyzed faster when compared to PET with 28% crystallinity. Ultrasound activation was found to be around three times more effective on powders vs. films most likely due to a larger surface area accessible to the enzyme.